Disseminated Nocardia Otitidiscaviarum in a Patient with AIDS - Roger M Sandre; Richard C Summerbell (Canadian Journal of Infectious Diseases)
A case of disseminated infection due to Nocardia otitidiscaviarum is described in a Caucasian man infected with the human immunodeficiency virus. The patient presented with no previous AIDS-defining conditions, a CD4 lymphocyte count of 206 cells/mm3 and enlarging intra-abdominal and chest wall abscesses with bilateral pulmonary infiltrates. Aggressive surgical debridement and antimicrobial therapy with trimethoprim/sulfamethoxazole and amikacin resulted in clinical cure. Long term suppressive therapy was needed to prevent relapse.